If A and B are square matrices of the same order such that AB = BA, then prove by induction that ABn = BnA. Further, prove that (AB)n = AnBn for all n ϵ N.
To prove: ABn = BnA
Given A and B are square matrices of same order such that AB = BA.
We have to prove it using mathematical induction.
Steps involved in mathematical induction are-
1. Prove the equation for n=1
2. Assume the equation to be true for n=k, where k ϵ N
3. Finally prove the equation for n=k+1
Let P(n): ABn = BnA
For n=1,
L.H.S: ABn = AB1 = AB
R.H.S: BnA = B1A = BA = AB
So, L.H.S = R.H.S
∴ P(n) is true for n=1.
Now assuming P(n) to be true for n=k, where k ϵ N
P(k): ABk = BkA …… (1)
Now proving for n=k+1, i.e. P(k+1) is also true
L.H.S = ABn
= ABk+1
= (ABk).B
= (BkA).B …… from (1)
= Bk(A.B)
= Bk(BA) (∵AB = BA)
= Bk+1A
R.H.S = BnA
= Bk+1A
∴ L.H.S = R.H.S
All conditions are proved. Hence P(k+1) is true.
∴ By mathematical induction we have proved that ABn = BnA.
Now, to prove: (AB)n = AnBn for all n ϵ N
For n=1,
L.H.S = (AB)n = (AB)1 = AB
R.H.S = AnBn = A1B1 = AB
∴ L.H.S = R.H.S
∴ It is true for n=1
Assuming it to be true for n=k then,
(AB)k = AkBk ……(2)
Now proving for n=k+1,
L.H.S = (AB)n
= (AB)k+1
= (AB)k(AB)1
= (AkBk)AB
= Ak(Bk.A)B
= Ak(A.Bk)B (ABn = BnA)
= (AkA)(BkB)
= Ak+1Bk+1
R.H.S = AnBn
= Ak+1Bk+1
∴ L.H.S = R.H.S
All conditions are proved. Hence P(k+1) is true.
∴ By mathematical induction we have proved that (AB)n = AnBn for all nϵN
Hence proved.